Pengaruh Kepemimpinan Dan Komunikasi Terhadap Kinerja Karyawan Properti - Sakhroni, Imam; Alamsyah, Thoriq; Wahjono, Sentot Imam (JURNAL EKONOMI, MANAJEMEN, BISNIS, DAN SOSIAL (EMBISS), 2025)
in a competitive business era, organizational performance is crucial for sustainability and relevance. This research explores the role of leadership and communication in enhancing employee performance. Leadership is more than just a position; it encompasses the ability to motivate and lead employees, thereby influencing their motivation and performance. Theoretical research identifies leadership styles, such as transformational and transactional leadership styles, which play a crucial role in creating a positive work environment. Effective communication as the foundation of the relationship between managers and employees involves conveying information, listening with empathy, and ensuring mutual understanding. Good communication creates a collaborative work environment, supports the organization's vision, and enhances performance. Challenges such as resistance to change highlight the need for continuous research and development to improve the quality of leadership and communication. A deep understanding of these dynamics supports the development of adaptive and effective strategies to support organizations in a dynamic business environment..